Student Religious Moderation Contest at Indonesian Islamic Universities - Adlan Fauzi Lubis; Saiful Bahri; Ayuhan Ayuhan (AL-ISHLAH: Jurnal Pendidikan, 2022)
Students' religious attitudes towards the state are still considered low, and there are even some students who refer to the state as toghut. However, the student's religious moderation is actually the key in realizing tolerance both at the national and international levels. The purpose of this study is to investigate the perspective of the moderate group of students on national commitment in Islamic universities. This study uses a qualitative method of descriptive analysis with data collection techniques in the form of interviews, observations, and document studies. The results showed that religious moderation among students of Islamic Religious Education, Faculty of Islamic Religion, Muhammadiyah University, Jakarta, did not have a negative connotation. Students have a tawasuth attitude that is not extreme left and right and more open in accepting religious arguments.